2022
DOI: 10.4103/jehp.jehp_38_22
|View full text |Cite
|
Sign up to set email alerts
|

Digital technology for facilitating inquiry-based learning during the COVID pandemic for human anatomy course

Abstract: BACKGROUND: Linking anatomy with the clinical approach for creating an inquisitive mind for a millennium via the digital platform is the need of the hour. Traditional lecturing makes students have rote memorization of the human anatomy. The inquiry-based project will allow undergraduate medical students to have a deeper understanding of human anatomy along with team building and interpersonal skill development. This approach of teaching would allow students to link the content taught for human ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…To address these issues, we propose the adoption of a “hybrid + flipped” teaching method based on BOPPPS to reform the curriculum. This method combines classroom teaching with online learning, leveraging independent learning and introductions to stimulate students' curiosity (Ahmad et al, 2020; Çakmakkaya et al, 2024; Wach et al, 2024); it also uses participatory learning to enhance their practical application abilities (Bellier et al, 2023; Vedi et al, 2022) and employs assessments and summarizations to consolidate their knowledge and skills (Kingston et al, 2023). The proposed method aims to improve students' clinical application skills, self‐directed learning abilities, and overall engagement with the course, goals which are consistent with a majority of the research on this topic (Alshawish et al, 2021; Bellier et al, 2023; Çan & Toraman, 2022; Thompson & Lake, 2023; Vedi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, we propose the adoption of a “hybrid + flipped” teaching method based on BOPPPS to reform the curriculum. This method combines classroom teaching with online learning, leveraging independent learning and introductions to stimulate students' curiosity (Ahmad et al, 2020; Çakmakkaya et al, 2024; Wach et al, 2024); it also uses participatory learning to enhance their practical application abilities (Bellier et al, 2023; Vedi et al, 2022) and employs assessments and summarizations to consolidate their knowledge and skills (Kingston et al, 2023). The proposed method aims to improve students' clinical application skills, self‐directed learning abilities, and overall engagement with the course, goals which are consistent with a majority of the research on this topic (Alshawish et al, 2021; Bellier et al, 2023; Çan & Toraman, 2022; Thompson & Lake, 2023; Vedi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This method combines classroom teaching with online learning, leveraging independent learning and introductions to stimulate students' curiosity (Ahmad et al, 2020; Çakmakkaya et al, 2024; Wach et al, 2024); it also uses participatory learning to enhance their practical application abilities (Bellier et al, 2023; Vedi et al, 2022) and employs assessments and summarizations to consolidate their knowledge and skills (Kingston et al, 2023). The proposed method aims to improve students' clinical application skills, self‐directed learning abilities, and overall engagement with the course, goals which are consistent with a majority of the research on this topic (Alshawish et al, 2021; Bellier et al, 2023; Çan & Toraman, 2022; Thompson & Lake, 2023; Vedi et al, 2022). Numerous studies conducted worldwide have highlighted the advantages of blended learning, which has been shown to enhance student performance and increase satisfaction (Al‐Hatem et al, 2018; Alvarez et al, 2017; Leidl et al, 2020; McCutcheon et al, 2018; Schurr et al, 2022; Verkuyl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As the quality of TEL resources has evolved, there are greater opportunities for students to use digital resources outside of the classroom [ 2 , 3 ]. This development combined with less time allocated to anatomy teaching, lack of cadavers, and larger student cohorts with a different mindset towards technology [ 4 – 7 ] as well as the recent pandemic has also pushed educators to use distant modes to deliver anatomy education [ 8 10 ]. Clunie et al studied evaluation approaches used to assess the impact of TEL within anatomy education and showed that most studies reported learner satisfaction followed by effects on learning outcomes at the module or course level [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that studies show that less time is currently allocated to anatomy teaching, combined with a lack of cadavers and larger student cohorts with a different mindset towards technology (17,18,19,20), TEL presents an opportunity for new approaches to learning. In addition, the recent pandemic also pushed educators to try a wide range of new approaches and use digital modes to deliver anatomy education (21,22,23). As the quality of TEL resources has evolved, there are greater opportunities for students to use these resources outside of the classroom (24,2).…”
Section: Introductionmentioning
confidence: 99%